Cattle mortality due to poisoning in Spain: a cross-sectional epidemiological study - García-Arroyo, Ricardo; Míguez, Maria-Prado; Hevia, María-Luisa; Quiles, Alberto (Spanish Journal of Agricultural Research, 2015)
The lack of nationwide public databases on poisoning in cattle makes it difficult to investigate this issue. Hence, we conducted an epidemiological study using the data on cattle poisoning provided by an insurance company (2000-2005), to determine the mortality rate due to poisoning in cattle in Spain and to assess the influence of the following variables: type of farming, age, sex, time of year, year and region. We observed a mortality rate of 23.25 per 100,000 animals in Spain with a higher rate in beef than dairy cattle (32.14 vs. 4.51 per 100,000 animals). There were also differences in the mortality rate between breeding cattle and future breeders, affecting dairy and beef cattle in a different way. In dairy cattle, we found differences between the years analysed. In beef cattle, the time of year with highest risk of poisoning was the last quarter (19.45 per 100,000 animals), while the lowest mortality rate was observed in the first quarter (1.33 per 100,000). There were pronounced differences between regions in beef cattle, differences being non-significant in dairy cattle. Lastly, in beef cattle, no differences were found between sexes. In summary, the mortality rate due to poisoning in cattle in Spain is low, and the risk of poisoning is determined by the farming system, animals’ stage of development, time of year and region.